2006
DOI: 10.1111/j.1468-5957.2006.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraday Price Discovery in the DJIA Index Markets

Abstract: This paper explores the dynamics of price discovery between the Dow Jones Industrial Average (DJIA) index and its three derivative products: the DIAMOND exchange-traded fund (ETF), the floor-traded regular futures, and the electronically traded mini futures. Even though the American Stock Exchange is the primary listing exchange for the ETF, the analysis indicates that the electronically traded ETF on the Archipelago (ArcaEx) electronic communications network dominates the price discovery process for DIAMOND s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 37 publications
7
55
0
Order By: Relevance
“…Using data (obtained from Bloomberg) at the 1-second frequency (a resolution used in several recent papers, e.g. Tse et al 2006) we found that the serial correlation of DAX returns exceeded 0.1 in six out of the ten trading days (March 7 -18, 2011) we considered. S , the slope is constant and equal to one, whereas the intercept changes daily.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using data (obtained from Bloomberg) at the 1-second frequency (a resolution used in several recent papers, e.g. Tse et al 2006) we found that the serial correlation of DAX returns exceeded 0.1 in six out of the ten trading days (March 7 -18, 2011) we considered. S , the slope is constant and equal to one, whereas the intercept changes daily.…”
Section: Discussionmentioning
confidence: 97%
“…Hasbrouck (2003) and Schlusche (2009) find that the futures market dominates price discovery. Tse et al (2006) report more differentiated results. The contribution of the ETF market to price discovery is negligible when ETF prices from a floor-based trading system (the Amex) are used.…”
mentioning
confidence: 91%
“…Nam et al (2006) explore the Korean market and document that both index futures and options lead the Korea Composite Stock Price Index 200 stock index. Similarly, Tse et al (2006) find that three different Dow Jones Industrial Average (DJIA) futures contracts contribute more to price discovery than the DJIA stock index. Garbade and Silber (1979), Harris et al (1995) and Hasbrouck (1995) focus on the securities traded across different markets and find that prices on the New York Stock Exchange lead the regional exchanges.…”
Section: Literaturementioning
confidence: 95%
“…However, Tse, Bandyopadhyay and Shen (2006) show that electronically traded Dow Jones ETFs contributes significantly to the price discovery process relative to the Dow futures. Therefore, instead of asking which instrument dominates price discovery, the more relevant question to ask is what characteristics and market conditions cause one instrument to provide a greater contribution to the price process?…”
mentioning
confidence: 97%
“…(2003) versus Tse, Bandyopadhyay and Shen (2006). Using both U.S. equity index futures and ETF data, Hasbrouck determines that the e-mini S&P 500 futures contributes more to price discovery than does the floor-traded SPY ETF.…”
mentioning
confidence: 99%